Molecular Analysis of Pregnancy Failure Due to Coxiella Burnetii (Coxielosis) in Women from Kut City - Shamkhi, Gufran J.; Alali, Sheama (Journal of Science in Medicine and Life, 2024)
The current research focused on investigating the occurrence of Coxiella burnetii infections by analyzing the frequency of positive cases in particular age groups and geographical areas. Encouraging findings were observed among individuals aged 21-26 years, highlighting a significant detection rate and emphasizing the need for further investigation into infection susceptibility and preventive measures in this age range. Similar trends were noticed in other age intervals, underlining the importance of raising awareness and implementing targeted prevention strategies across different age brackets. Furthermore, variations in infection rates between urban and rural areas suggest differing transmission risks, possibly attributed to environmental factors and occupational exposures. Various studies have identified risk factors such as contact with infected animals and specific animal reservoirs. Pregnant women are particularly vulnerable to Coxiella burnetii infections, emphasizing the significance of considering regional factors and implementing preventive measures. Overall, this research underscores the need for further investigation and the implementation of targeted prevention strategies to mitigate the risk of Coxiella burnetii infections and improve public health outcomes.